Research of Synergistic Substances on Tobacco Beetle [Lasioderma serricorne (Fabricius) (Coleoptera: Anobiidae)] Adults Attractants - Ren, Yanling; Wang, Tao; Jiang, Yingjie; Chen, Pengchao; Tang, Jian; Wang, Juan; Jin, Daochao; Guo, Jianjun (Frontiers in Chemistry, 2022)
In this study, 4 kinds of chemical substances (2,3,5,6-tetramethylpyrazine, β-ionone, citronellal, and paeonol), 3 kinds of plant essential oils (tea tree essential oil, lavender essential oil, and myrrh essential oil), and their combinations were selected to explore their synergistic effects on tobacco beetle (Lasioderma serricorne (Fabricius) (Coleoptera: Anobiidae)) adults by the behavioral test and laboratory simulation test. Behavioral test results showed that some of the combinations revealed a synergistic effect on tobacco beetle adults, especially, the sexual attractant + 2,3,5,6-tetramethylpyrazine + β-ionone + citronellal + paeonol (SABCD, 1 portion sexual attractant and 1 mg/L synergistic substance) combination and food attractant + 2,3,5,6-tetramethylpyrazine + paeonol (FAD, 1 mL food attractant and 1 mg/L synergistic substances) combination showed the best behavioral effect on tobacco beetle adults with the average dwell time of 120.97 and 126.74 s, respectively, than those of other combinations. Meanwhile, SABCD had the highest selection rate (89.47%, about 1.5 times than sexual attractant (S)) on tobacco beetle adults compared with those of other combinations. In addition, laboratory simulation test results showed that the SABCD combination had the highest average selection rate (37.31%, about 2 times than S) on tobacco beetle adults at 1 mg/L. However, our results showed that there was no significant difference in the indoor simulation results of food attractant synergistic substances. Our results will provide a guidance for the development of new pesticides for tobacco beetle adults.